Pharmacological chaperones for human α-N-acetylgalactosaminidase. - Clark, N; Metcalf, M; Best, D; Fleet, G; Garman, S (2012)
Schindler/Kanzaki disease is an inherited metabolic disease with no current treatment options. This neurologic disease results from a defect in the lysosomal α-N-acetylgalactosaminidase (α-NAGAL) enzyme. In this report, we show evidence that the iminosugar DGJNAc can inhibit, stabilize, and chaperone human α-NAGAL both in vitro and in vivo. We demonstrate that a related iminosugar DGJ (currently in phase III clinical trials for another metabolic disorder, Fabry disease) can also chaperone human α-NAGAL in Schindler/Kanzaki disease. The 1.4- and 1.5-Å crystal structures of human α-NAGAL complexes reveal the different binding modes of iminosugars compared with glycosides. We show how differences in two functional groups result in >9 kcal/mol of additional binding energy and explain the molecular interactions responsible for the unexpectedly high affinity of the pharmacological chaperones. These results open two avenues for treatment of Schindler/Kanzaki disease and elucidate the atomic basis for pharmacological chaperoning in the entire family of lysosomal storage diseases.